KAMPANYE KHILAFATUL MUSLIMIN DALAM PERSPEKTIF SIYASAH DUSTURIYAH - Arafah, Reza Kurniawan; Khalik, Subhan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The aim of this research is to analyze the Khilafatul Muslimin campaign from the perspective of Siyasah Dusturiyah. The problem is the emergence of the Khilafatul Muslimin organization's campaign which is contrary to the Pancasila ideology. This type of research is Library Research using a normative juridical approach. The data sources used in this research are secondary data sources, namely data such as books related to the research subject, research reports, papers, dissertations, and statutory regulations. Data processing and analysis techniques are: data display, editing, finding, data analysis and conclusion. Data analysis is by carrying out analysis both in terms of content, legality, whether carried out textually or conceptually based on literature studies and the study of statutory regulations by studying every norm that exists in the view of Islamic Constitutional Law (Siyasah Syar'iyyah) . The results of this research show: The campaign carried out by Khilafatul Muslimin is a form of movement in declaring an Islamic state so that Khilafatul Muslimin is subject to sanctions for disbanding mass organizations. The pattern of spreading the ideology of the caliphate carried out by the Khilafatul Muslimin was spread in various ways, including da'wah. The spread of ideologies that are at odds with Pancasila is also carried out through open campaigns, such as convoys, monthly recitations and the Internet.